Curcumin encapsulation in yeast glucan particles promotes its anti-inflammatory potential in vitro - Plavcová, Zuzana; Šalamúnová, Petra; Saloň, Ivan; Štěpánek, František; Hanuš, Jaroslav; Hošek, Jan (International journal of pharmaceutics, 2019)
Glucan particles (GPs) from Saccharomyces cerevisiae are hollow shells that are composed mainly of β-1,3-d-glucan, which has demonstrated immunomodulatory and anti-inflammatory potential both in vitro and in vivo. Curcumin is a natural hydrophobic phenolic compound, which possesses a significant anti-inflammatory effect and is used as supportive therapy in the treatment of many inflammatory diseases. The aim of this study is to evaluate the possible synergic effect and other benefits of the co-application of GPs and curcumin in the form of pharmaceutical composites. GP/curcumin composites were prepared using controlled evaporation of the organic solvent and their anti-oxidative effect and anti-inflammatory potential were tested on THP1‑XBlue™‑MD2‑CD14 human monocytes cell line. The anti-oxidative effect was measured on pyocyanin-stimulated cells in vitro and the NF-κB/AP-1 signaling pathway on lipopolysaccharide pre-treated monocytes was chosen for anti-inflammatory assays. The secretion of pro-inflammatory cytokines TNF-α and IL-1β was evaluated as well. Results mostly showed a pro-oxidative activity of empty GPs, however, pharmaceutical composites demonstrated an anti-oxidative effect. The activity of NF-κB/AP-1 was substantially decreased by the tested GP/curcumin composites, which also caused the attenuation of cytokines secretion. The obtained results indicate a beneficial effect of the incorporation of curcumin into GPs.
Keywords: Cell Survival; reaktivní formy kyslíku; Interleukin-1beta; Humans; Transcription Factor AP-1; antiflogistika; Drug carrier; lipopolysacharidy; Lipopolysaccharides; makrofágy; Inflammation; Pharmaceutical composite; lidé; kurkumin; Reactive Oxygen Species; THP-1 buňky; β-Glucan microparticles; Glucans; TNF-alfa; Curcumin; interleukin-1beta; Saccharomyces cerevisiae; Monocytes; Tumor Necrosis Factor-alpha; Anti-Inflammatory Agents; glukany; monocyty; NF-kappa B; Macrophages; transkripční faktor AP-1; THP-1 Cells; viabilita buněk